EFEKTIVITAS METODE PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS IX SMP NEGERI 1 PADANG GELUGUR KABUPATEN PASAMAN - Andria Catri Tamsin, Ahmad Rawi, Erizal Gani, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study is (1) to describe the skill of writing a short story class IX students of SMPN I Padang gelugur Pasaman of before and after using the learning method cooperatif Type Cooperative Integrated Reading and Composition. (2) describe the effectiveness of teaching methods CIRC against short story writing skills class IX students of SMP Negeri I Padang gelugur Pasaman district. This research is a quantitative study with a quasi-experimental methods (quasi experiment). Data of this study was the result of tests short story writing skills of students before and after using cooperative learning methods CIRC (posttest) class IX students of SMP Negeri I Padang gelugur Pasaman district. Based on the results of the study, concluded the following three points. (1) short story writing skills before using cooperative learning methods CIRC class IX students of SMPN I Padang gelugur Pasaman is currently on qualification More than Enough (LDC) with an average value of 63.31. (2) the skill of writing short stories after using cooperative learning methods CIRC class IX students of SMPN I Padang gelugur Pasaman is currently on the qualification Good (B) with an average value of 82.79. (3) based on the t-test results, it was concluded that the alternative hypothesis (H1) is accepted at level siginifikansi 95% and degrees of freedom (df) = n - 2 for thitung> t table (3.22> 1.70).Â Keywords: Â efektifitas, kooperatif tipe CIRC, menulis cerpen